(untitled) (Baghdad Science Journal, 2023)
This research presents a statistical study of radiation generated from communication towers in the Nineveh Plain region Baghdeda. The intensity of radiation energy was measured at 10 meters away from the communication tower in different locations, using a (1PC XH-901 Dosimeter/ Personal Dose Alarm / Radiation Detector, dosage rate: 0.01 μSv/h to 150μSv/h) to measure the amount of radiation at various times. Energy densities were measured and compared with standard limits provided by other authorities, such as the International Committee for Radiation Protection. Results were analyzed using SPSS version 26 to implement the data. The results show that the means of the radiation levels measured at all the zones do not statistically differ from the highest values determined globally 0.50-1.70 μSv/y; they lie within the radiation-free zones. Civilians may not always have a choice where the mobile tower will place. As a result, it may rely on some quick fixes, such as certified radiation protection items that offer all-around protection from mobile tower irradiance. The radiation shielding technology used in these goods alters the nature of irradiation from a constant to a variable waveform, rendering it useless.